Direct Oral Anticoagulants Versus Vitamin K Antagonists in Cerebral Venous Thrombosis: A Systematic Review and Meta-Analysis. Issue 10 (8th August 2022) - Yaghi, Shadi; Saldanha, Ian J.; Misquith, Chelsea; Zaidat, Bashar; Shah, Asghar; Joudi, Kareem; Persaud, Bianca; Abdul Khalek, Feras; Shu, Liqi; de Havenon, Adam; Mistry, Eva A.; Bakradze, Ekaterina; et al.
Abstract : Background: High level evidence for direct oral anticoagulants (DOACs) in patients with cerebral venous thrombosis is lacking. We performed a systematic review and meta-analysis to assess the efficacy and safety of DOACs versus vitamin K antagonists in patients with cerebral venous thrombosis. Methods: This systematic review was registered in PROSPERO (CRD42021228800). We searched MEDLINE (via Ovid), EMBASE, CINAHL, and the Web of Science Core Collection between January 1, 2007 and Feb 22, 2022. Search terms included a combination of keywords and controlled vocabulary terms for cerebral venous thrombosis, vitamin K antagonists/warfarin, and DOACs. We included both randomized and nonrandomized studies that compared vitamin K antagonists and DOACs in 5 or more patients with cerebral venous thrombosis. Where studies were sufficiently similar, we performed meta-analyses for efficacy (recurrent venous thromboembolism and complete recanalization) and safety (major hemorrhage) outcomes, using relative risks (RRs). Results: Out of 10 665 records identified, we screened 254 as potentially eligible. Nineteen studies (16 observational studies [n=1735] and 3 randomized controlled trials [n=215]) met the inclusion criteria. All 3 randomized controlled trials had some concerns, and all 16 observational studies had at least moderate risk of bias. When compared with vitamin K antagonist treatment, DOAC had comparable risks of recurrent venous thromboembolism (relative risk [RR], 0.85 [95% CI, 0.52–1.37], I 2 =0%), major hemorrhage (RR, 0.70 [95% CI, 0.40–1.21], I 2 =0%), intracranial hemorrhage (RR, 0.58 [95% CI, 0.30–1.12]; I 2 =0%), death (RR, 1.14 [95% CI, 0.54–2.43], I 2 =1%), and complete venous recanalization (RR, 0.98 [95% CI, 0.87–1.11]; I 2 =0%). Conclusions: This systematic review and meta-analysis suggest that in patients with cerebral venous thrombosis, DOACs, and warfarin may have comparable efficacy and safety. Given the limitations of the studies included (low number of randomized controlled trials, modest total sample size, rare outcome events), our findings should be interpreted with caution pending confirmation by ongoing randomized controlled trials and large, prospective, observational studies.